Japan : Oversight and Supervision of Financial Market Infrastructures (FMIs): Technical Note. (IMF Staff Country Reports; Country Report, 2012)
The report focuses on the role played by financial market infrastructures (FMIs) in maintaining and promoting financial stability in Japan. FMIs are important tools that contribute to the Japanese financial sector, especially in the domain of domestic financial stability. The oversight and supervision framework of important FMIs are discussed and analyzed. Even though the supervision of FMIs is fragmented, the report highlights the measures to be taken to strengthen the effectiveness of FMIs.